A retrospective chart review of trauma‐related documentation in an Australian substance use treatment service. (14th November 2022) - Harvey, Logan R.; Hopkins, Rachel; Truscott, Melanie; Marel, Christina; Slade, Tim; Mills, Katherine L.
Abstract: Introduction: Trauma exposure among clients of substance use treatment services is almost universal and rates of trauma‐related symptoms are correspondingly high. This study examined one aspect of clinical care—clinical documentation—and sought to systematically assess the documentation of trauma‐related comorbidities and their treatment in a substance use treatment setting. Methods: A retrospective chart review was conducted on a sample of 300 patient records in a public substance use treatment setting. Rates of documentation of trauma‐related events, symptoms and treatment, along with variables influencing the documentation of these issues, were examined. Results: Trauma‐related documentation was present in 45.3% of records. There were documented trauma‐related symptoms in 15.3% of records, although treatment activities addressing trauma were only present in 2.3% of records. Being female (odds ratio [OR] 2.58, 95% confidence interval [CI] 1.42, 4.69), having prior mental health treatment (OR 1.82, 95% CI 1.05, 1.12) and having more treatment sessions (OR 1.08, 95% CI = 1.05, 1.12) increased the odds of trauma‐related documentation being present, while being in the first episode of treatment (OR 0.49, 95% CI = 0.28, 0.84) decreased the odds. Discussion and Conclusions: This study highlights significant under documentation of trauma‐related comorbidities in substance‐use treatment. There is limited evidence of consideration of trauma‐related symptoms or diagnoses, and trauma‐related comorbidities are rarely included in treatment planning activities. The lack of documented trauma‐related information has important clinical and medico‐legal implications for patients, and provides evidence to suggest a lack of integration of treatment for trauma‐related disorders in substance use settings.